Toxin MqsR cleaves single‐stranded mRNA with various 5' ends. Issue 3 (5th February 2016) - Chowdhury, Nityananda; Kwan, Brian W.; McGibbon, Louise C.; Babitzke, Paul; Wood, Thomas K.
Abstract: Toxin/antitoxin (TA) systems are the means by which bacterial cells become persistent; that is, those cells that are tolerant to multiple environmental stresses such as antibiotics by becoming metabolically dormant. These persister cells are responsible for recalcitrant infections. Once toxins are activated by the inactivation of antitoxins (e.g., stress‐triggered Lon degradation of the antitoxin), many toxins reduce metabolism by inhibiting translation (e.g., cleaving mRNA, reducing ATP). The MqsR/MqsA TA system of Escherichia coli cleaves mRNA to help the cell withstand oxidative and bile acid stress. Here, we investigated the role of secondary structure and 5′ mRNA processing on MqsR degradation of mRNA and found that MqsR cleaves only single‐stranded RNA at 5′‐GCU sites and that MqsR is equally active against RNA with 5′‐triphosphate, 5′‐monophosphate, and 5′‐hydroxyl groups. Abstract : Using RNA that is single‐stranded, double‐stranded, or folds into a stem loop or pseudoknot, we found that toxin MqsR of the MqsR/MqsA TA system cleaves primarily single‐stranded RNA. Furthermore, we found that 5′ processing is not required for the RNA to be a substrate since MqsR has activity on RNA with 5′‐ppp, 5′‐p and 5′‐OH ends. Hence, MqsR cleavage of mRNA does not depend on preprocessing by RNA pyrophosphohydrolase (RppH) to remove pyrophosphate like RNase E, the primary enzyme for mRNA turnover, which implies that once activated by stress, toxin MqsR can rapidly degrade nearly all the mRNA (all but 14 Escherichia coli transcripts have 5′‐GCU sites) as well as possibly tRNA and rRNA.